(untitled) (Al-Qamar, 2019)
This article studies jurisprudential discussions in the Exegesis of Surah al-Nisāʻ from “Taisīr al-Quran” by ʻAbd al-Raḥmān Kilānī (1923-1988), a Pakistani commentator of the Quran. It discusses the issues of permission for four marriages for men, rulings relating to the property of orphans, share of inheritance of women and children, rulings on inheritance of Kalāla, issue of inheritance of orphan grandson, witness of adultery, punishment of homosexuality, repentance, prohibition of marriage to stepmothers, rulings on breastfeeding, Maharams, prohibited relationships with Sunnah, rulings on concubines, prohibition of Mutʻah marriage, prohibition of Interest, lottery and Insurance, supremacy of men over women, prohibition of alcohol etc. From these discussions, it is clear that the commentator has tried to present the Islamic position on the relevant issues in a systematic manner by giving important information in the jurisprudential discussions and by understanding the relevant topics in a modern context.